Effectiveness of face-to-face and facebook collaborative writing in Malaysian ESL undergraduates' writing performance - Shukor, Siti Shuhaida (2014)
This study investigated the effects of Facebook collaborative writing on a group of English as Second Language (ESL) undergraduates'a writing participants of the study were 33 second year ESL undergraduates at the Faculty of Educational Studies, Universiti Putra Malaysia. They were categorized into two groups i.e. experimental and comparison groups using the matching-only design. The experimental group was assigned to Facebook collaborative writing tasks while the comparison group was assigned with face-to-face tasks. Face-to-face is considered as the conventional method in this study. This study employed a quasi experimental design with quantitative data. Instruments of the study were pre- and post- writing tests, as well as a set of questionnaire. The fieldwork was conducted in one semester. Data obtained were analyzed using descriptive statistics such as mean scores, standard deviations, frequency and percentages while inferential statistics such as independent sample t-test and paired sample t-test were utilized in finding the mean differences in the writing performance. The findings of the study indicate that there were no significant differences in the overall post-test writing performance between face-to-face and Facebook collaborative writing and similar findings were found in content, organization, vocabulary, language use and mechanics. However, when the mean scores were compared within each group, for face-to-face collaborative writing, it was found that there were significant differences for overall writing performance (t=-3.523, p=.003), content (t=-5.694 p=.000), organization (t=-2.743,p=.014) and vocabulary (t=-3.536, p=.003) except for language use and mechanics. Meanwhile for Facebook collaborative writing, there were significant differences for overall writing performance (t=-6.864, p=.000), content (t=-8.035, p=.000),organization (t=-5.730, p=.000), vocabulary (t=-3.083, p=.008), language use (t=-3.301, p=.005) and mechanics (t=-2.711, p=.016) as well. Besides, perceptions towards Facebook collaborative writing were also found to be fairly positive with the aggregated scores ranging from (M= 3.00 to M= 3.18). As a conclusion, Facebook collaborative writing was proven to be a good platform in ESL learning context. The role of Facebook collaborative writing in writing performance was statistically and practically significant.